"America First" and the Return of Economic Isolationism and Nationalism to the United States: A Historic Turning Point for International Trade Law. (12th November 2020) - DUFOUR, GENEVIÈVE; DUCASSE, DELPHINE
Abstract: American trade policy under the Trump administration can be summed up in one expression, "America First, " which the US president himself has repeated many times. Driven by a rejection of multilateralism, the United States has adopted numerous measures designed to maintain or stimulate domestic industry or to tighten economic policies both domestically and towards foreign trading partners. Reflecting isolationist and nationalist economic theories, these measures are the anchor for a return of economic frontiers to the United States. Yet the United States is at the heart of globalization and cannot completely isolate itself without risking an economic meltdown. This is all the more true since it has been the driving force behind the creation of the multilateral trading system since the end of the Second World War. This change of economic vision by one of the world's greatest powers can only be a turning point in the recent history of international economic relations. As such, one may wonder whether America First and the set of measures adopted in its name also foreshadow a phase of retreat for international trade law or whether, on the contrary, they are an opportunity for reform of an area of the law that has been struggling to evolve for several decades.